Papel antiviral do peptídeo AHD na infecção pelo virus da dengue - Ingredy Beatriz Souza Passos (2021)
Due to the co-circulation and hyper-endemicity of multiple dengue virus serotypes in several countries, dengue has become the arbovirus with the highest incidence and geographic expansion. It is estimated that half of the world's population lives in areas at risk for infection. Infection with one of the four dengue virus serotypes causes a wide spectrum of clinical manifestations that range from asymptomatic, mild and/or similar to other viral infections to intense/severe manifestations that can lead to death. It is a disease without specific treatment, responsible for a high number of hospitalizations, with an increasing mortality rate and representing an important public health problem. Thus, the development of prophylactic and therapeutic measures, as well as the study of the mechanisms by which the disease is established and the events involved in the virus-host interaction are essential points for advancing in the management of dengue. In this context, the aim of the present work was to evaluate the antiviral activity of the AH-D peptide, with known antiviral activity against other related flaviviruses, in the course of dengue virus infection. For this purpose, two experimental strategies were used - I) The cytotoxicity of the samples was initially evaluated in Vero CCL-81 cells, which were used in the assay of antiviral activity in the presence or absence of the AH- D peptide. II) In vivo evaluation of the antiviral potential of the AH-D peptide. For this purpose, knockout mice for the gene encoding the α/β Interferon Type-I receptor (A129) infected by DENV and their respective controls were used. At different times after infection, the animals were treated with the antiviral peptide intravenously. Afterwards, several parameters were analyzed, namely i) viral load in different tissues; ii) clinical and inflammatory parameters; iii) and, survival curve in order to evaluate the effectiveness of the peptide in this model. Our results demonstrate that treatment with the AH-D peptide in Vero CCL-81 cells resulted in a dose-dependent reduction in viral load and a reduction in cell death. In vivo, the intravenous administration of the peptide did not result in a reduction in viral loads, as observed in vitro, however there was an improvement in clinical parameters such as the prevention of loss of body mass and thrombocytopenia, in addition to the lethality in these animals. Overall, treatment with AH-D was able to prevent the main manifestations induced by DENV infection.